Network meta-analysis of randomized controlled trials on esophagectomies in esophageal cancer The superiority of minimally invasive surgery - Szakó Lajos (WORLD JOURNAL OF GASTROENTEROLOGY, 2022)
Previous meta-analyses, with many limitations, have described the beneficial nature of minimal invasive procedures.To compare all modalities of esophagectomies to each other from the results of randomized controlled trials (RCTs) in a network meta-analysis (NMA).We conducted a systematic search of the MEDLINE, EMBASE, Reference Citation Analysis (https://www.referencecitationanalysis.com/) and CENTRAL databases to identify RCTs according to the following population, intervention, control, outcome (commonly known as PICO): P: Patients with resectable esophageal cancer; I/C: Transthoracic, transhiatal, minimally invasive (thoracolaparoscopic), hybrid, and robot-assisted esophagectomy; O: Survival, total adverse events, adverse events in subgroups, length of hospital stay, and blood loss. We used the Bayesian approach and the random effects model. We presented the geometry of the network, results with probabilistic statements, estimated intervention effects and their 95% confidence interval (CI), and the surface under the cumulative ranking curve to rank the interventions.We included 11 studies in our analysis. We found a significant difference in postoperative pulmonary infection, which favored the minimally invasive intervention compared to transthoracic surgery (risk ratio 0.49; 95%CI: 0.23 to 0.99). The operation time was significantly shorter for the transhiatal approach compared to transthoracic surgery (mean difference -85 min; 95%CI: -150 to -29), hybrid intervention (mean difference -98 min; 95%CI: -190 to -9.4), minimally invasive technique (mean difference -130 min; 95%CI: -210 to -50), and robot-assisted esophagectomy (mean difference -150 min; 95%CI: -240 to -53). Other comparisons did not yield significant differences.Based on our results, the implication of minimally invasive esophagectomy should be favored.